Development of Beach Tourism in Teluk Gosong Village, Pulau Laut Timur District, Kotabaru Regency - Fachri Ubadiyah (Enrichment : Journal of Management, 2022)
The beaches in Teluk Gosong Village, with their beauty and nature, are very exotic, but unfortunately, these tourist objects still need to be managed and developed optimally. Based on this, the coastal tourism object of Teluk Gosong Village needs special attention for improvement and development. This study aims to determine the strategy for developing beach tourism objects in Teluk Gosong Village. The field research method was carried out by visiting each beach tourism object in the study area. The data collected is in the form of primary data and secondary data. The questionnaire was used as an interview aid. The collected data were analyzed using SWOT analysis. The strategy for developing coastal tourism objects in Teluk Gosong Village, which was put forward from the results of the study, were: (1) involving the district and provincial governments in the development and management of coastal tourism objects in Teluk Gosong Village (2) increasing community capacity through training for community managers (3) conducting promotions through online media facilities (4) construction of facilities and infrastructure, (5) cooperating with travel agents (travel agents), (6) building tourism awareness groups for the managing community (7) building playgrounds, (8) displaying various attractions including cultural and serving local cuisine, (9) disaster mitigation and (10) preserving and preserving the environment. This development strategy can be applied to the development of coastal tourism objects in Teluk Gosong Village, Pulau Laut Timur District, Kotabaru Regency, with the hope that along with the development of these tourism objects, the economy and welfare of the local community will also develop and increase